2021
DOI: 10.3389/fneur.2021.684362
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Language Functions in Patients With Disorders of Consciousness Using an Alternative Communication Tool

Abstract: This study aimed to describe the percentage of tasks involving language functions that were completed by patients diagnosed with disorders of consciousness, as observed during neurorehabilitation conducted for different periods of time using an alternative communication tool. The project involved six participants, who were observed for 1 month, 6 months, and 1 year. The patients were asked to solve tasks involving language functions with the use of an eye-controlled device. The language functions were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Recent neuroimaging research has demonstrated that some vegetative state patients can respond to commands by willfully modulating their brain activity according to instructions (Owen et al, 2006;Monti et al, 2010;Sun and Zhou, 2010). For example, Kujawa et al (2021) assessed the linguistic capabilities of a group of patients with unresponsive wakefulness syndrome caused by sudden circulatory arrest. They were asked to point to the picture they heard called (for example, "thermometer") and to choose the related pictogram among other objects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging research has demonstrated that some vegetative state patients can respond to commands by willfully modulating their brain activity according to instructions (Owen et al, 2006;Monti et al, 2010;Sun and Zhou, 2010). For example, Kujawa et al (2021) assessed the linguistic capabilities of a group of patients with unresponsive wakefulness syndrome caused by sudden circulatory arrest. They were asked to point to the picture they heard called (for example, "thermometer") and to choose the related pictogram among other objects.…”
Section: Discussionmentioning
confidence: 99%
“…Also, MR scanners are uncomfortable for patients with DoC. As a result, because these techniques are expensive, time-consuming and inconvenient to operate, behavioral test remains the best method for assessing human consciousness [25].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore reasonable to use eye tracking for medical purposes, for example in supporting neurological assessment of patients with severe communication barriers ( 37 ). An example of such studies is the assessment of language function in patients with impaired consciousness ( 38 ).…”
Section: Introductionmentioning
confidence: 99%